THE COMPARISON BETWEEN MONOTHERAPY AND POLYTHERAPY IN EPILEPSY IDIOPATHIC GENERALISED TONIC CLONIC - Ratna Wijayatri; Zullies Ikawati; Abdul Ghofir (JURNAL MANAJEMEN DAN PELAYANAN FARMASI (Journal of Management and Pharmacy Practice))
The prevalence of epilepsy in the world reachs 5-20 per 1000 population. In Indonesia, the prevalence of epilepsy is approximately at 0.5-1.2%. Antiepilepsy drug has an important role in the epilepsy treatment. This study was aimed to know the effectiveness and safety of monotherapy treatment compared to polytherapy in terms of seizure frequency, seizure-free duration, and adverse drug reaction. This study was the observational research. The data were collected prospectively using instruments i.e.: seizure diaries and APS (Adverse Drug Reaction Probability Scale). Subject of this study were epileptic patient with idiopathic generalized tonic clonic who receive either polytherapy or monotherapy in neurological clinic of Dr. Sardjito Hospital on May-June 2012 period, which fulfilled the inclusion criteria. The data from monotherapy and polytherapy group was analysed in term of seizure frequency, seizure-free duration and adverse drug reaction. Result showed that monotherapy treatment more effective in controlling seizure (reduce the frequency of seizure) compared to polytherapy (<0.05). Percentage of seizure free was 83% in monotherapy compared to 48% in polytherapy. The prevalence of adverse drug reaction was about 20% in monotherapy and 14% in polytherapy. Based on the interview, although monotherapy caused more adverse drug reaction than that in polytherapy, the drug adverse reaction in monotherapy was milder and did not annoy patient convenience.Keywords: Epilepsy, Idiopathic Generalised Tonic Clonic, Monotherapy, Polytherapy, Adverse Drug Reaction